Essential Characteristics for School Administrators in the Digital Age for Thailand - Tomun, Nattapong; Benjapitakdilok, Rapeeporn; Kaewjam, Prasert (Journal of Ecohumanism, 2024)
Introduction: It is well known that education and teaching practices are affected by technological developments. The ubiquitous spread of information and communication technologies in recent years has forced educational institutions to undergo a digital transformation so as to keep up with the today’s technological age. Educational activities have become sustainable in virtually all environments and under virtually all conditions, with interactive whiteboards having long since replaced the traditional blackboard in most schools. Changes emerging today include revised job definitions, changing patterns of daily life, and the desire for economic value; together they represent the primary results of this digital transformation. Objective: This study aims to explore the essential characteristic for school administrators in the digital age. Method: This is quantitative approach. The population was educational administrators in Thailand who are responsible for management in educational institutions. This Quantitative Research analyzed the data using Descriptive Statistics, Inference Statistic and Multivariate by IBM SPSS and Structural Equations Modeling (SEM) was analyzed by IBM SPSS AMOS. Results: 1) Government Policy (GP) 2) Performance Attribute (PA) and 3) Competent Innovation directly influence on Perceived Value. Moreover, Perceived Value directly influences on Performance Identification. Analysis of the SEM model was found to be accurate because the model is consistent with empirical data, harmonization index passed all criteria, Chi-Square = 173.53, df = 88 RMSEA = 0.04 and RMR = 0.03, index GIF = 0.96 and AGIF = 0.94 and R2/ df = 1.97. Conclusion: These findings can be used to develop academic fields such as research and strategic planning effectively and can be applied in educational industry as well, so making the product feature that meets the needs of the customer will result in the perception of the value of the product and making a purchase decision. This finding has benefits on human resources development and school management and school administrators as well.